Complications during removal of stainless steel versus titanium nails used for intramedullary nailing of diaphyseal fractures of the tibia. (February 2018) - Seyhan, Mustafa; Guler, Olcay; Mahirogullari, Mahir; Donmez, Ferdi; Gereli, Arel; Mutlu, Serhat
Abstract: Objectives: Intramedullary nailing is the treatment of choice for fractures of the tibial shaft, which might necessitate the nail removal due to complications in the long-term. Although considered as a low-risk procedure, intramedullary nail removal is also associated with certain complications. Here, we compared the most commonly used stainless steel and titanium nails with respect to the complications during removal and clinical outcome for intramedullary nailing of diaphyseal fractures of the tibia. Patients and methods: Sixty-two patients (26 females, 36 males) were included in this retrospective study. Of the removed nails, 24 were of stainless steel and 38 of titanium. Preoperative and intraoperative parameters, such as implant discomfort, anterior knee pain, operating time and amount of bleeding, and postoperative outcomes were evaluated for each patient. Results: Titanium nail group had more, but not statistically significant, intraoperative complications than stainless steel group during the removal of nails (p = .4498). Operating time and amount of intraoperative bleeding were significantly higher in titanium group than stainless steel group (p = .0306 and p < .001, respectively). Preoperative SF-36 physical component and KSS scores were significantly lower in patients who had removal of titanium nails than those of stainless steel nails, whereas there was no difference in terms of postoperative SF-36 and KSS scores. Conclusion: In conclusion, although greater bone contact with titanium increases implant stability, nail removal is more difficult, resulting in more longer surgical operation and more intraoperative bleeding. Therefore, we do not recommend titanium nail removal in asymptomatic patients. Highlights: Titanium nails increase implant stability but removal is difficult and complicated.